2019
DOI: 10.3390/rs11080900
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Land Surface Temperature Trends in the Central Himalayan Region Based on MODIS Products

Abstract: The scientific community has widely reported the impacts of climate change on the Central Himalaya. To qualify and quantify these effects, long-term land surface temperature observations in both the daytime and nighttime, acquired by the Moderate Resolution Imaging Spectroradiometer from 2000 to 2017, were used in this study to investigate the spatiotemporal variations and their changing mechanism. Two periodic parameters, the mean annual surface temperature (MAST) and the annual maximum temperature (MAXT), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 46 publications
2
50
0
Order By: Relevance
“…Consequently, it is highly important to understand the drought pattern in order to assist decision makers in preparing appropriate strategies for the changing conditions therein. Unfortunately, few stations are established in mountainous areas of the Central Himalaya, and usually they lack long-term records [31]. In response to the abovementioned limitations, satellite remote sensing provides spatially contiguous high-accuracy and high-resolution information, particularly in remote mountainous areas [31]; thus, remote sensing constitutes an alternative approach to monitoring the dynamics of drought.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is highly important to understand the drought pattern in order to assist decision makers in preparing appropriate strategies for the changing conditions therein. Unfortunately, few stations are established in mountainous areas of the Central Himalaya, and usually they lack long-term records [31]. In response to the abovementioned limitations, satellite remote sensing provides spatially contiguous high-accuracy and high-resolution information, particularly in remote mountainous areas [31]; thus, remote sensing constitutes an alternative approach to monitoring the dynamics of drought.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse gasses suppress cooling the earth surface by trapping terrestrial thermal radiation. Comparable results were reported in Nepal (Luintel et al, 2019;Zhao et al, 2019); the authors indicated that the mean annual LST and annual maximum LST in nighttime had mean change rates in the period 2000-2017 of about 0.048°C/year and 0.091°C/year, respectively. However, nighttime significant rates of increase obtained from the present study might be described as being faster than those obtained for Greece (Eleftheriou et al, 2018); the authors indicated that nighttime LST demonstrated increasing annual trends in the period 2000-2017 ranging from 4.6 × 10 −5 to 3.1 × 10 −3°C / year.…”
Section: Resultsmentioning
confidence: 52%
“…Accordingly, this study aims at determining the seasonalities and spatial and temporal rates of change of MODIS-based LST data and exploring whether these rates differ between daytime and nighttime in Jordana typical Middle Eastern semi-arid to arid country. Interestingly, the literature in this specific area of application is not at the desired level of ambitions and aspirations (Eleftheriou et al, 2018;Luintel, Weiqiang, Yaoming, Binbin, & Sunil, 2019;Mao et al, 2017;Sun, Wan, Imbery, Lotz, & King, 2015;Zhao et al, 2019), which makes this type of studies important in order to fill in this serious scientific gap. This study also aims at investigating whether the discerned daytime and nighttime spatial and temporal rates of change of MODIS-based LST in the study area are natural or anthropogenic.…”
Section: Introductionmentioning
confidence: 99%
“…The green corridor should be away from highways by creating buffer zones along the path to protect the wildlife and provides safe places for visitors (Alexandre et al, 2010). According to Figure 14, designing buffer zones along the green corridor as open spaces provide a vital area for all services needed by humans, attractive places for tourism, increase air quality, protect the natural environment, and enhance awareness of humans to protect wildlife The higher elevations have been shown a sharp difference in temperature less than lower elevation (Zhao et al, 2019). Jordan weather is dry hot and dry in summer and cold in the winter.…”
Section: Resultsmentioning
confidence: 99%